Lithium iron phosphate precursor material and preparation method thereof, lithium iron phosphate material and preparation method thereof, positive pole piece and secondary battery
By optimizing the composition and processing technology of lithium iron phosphate precursor materials, the problem of low energy density of lithium iron phosphate materials was solved, and high-capacity, high-density lithium iron phosphate materials were prepared, thereby improving the energy density of secondary batteries.
Patent Information
- Application Number
- CN202511014612.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-22
- Publication Date
- 2025-10-28
AI Technical Summary
Lithium iron phosphate materials have low energy density, which cannot meet the market demand for energy density in secondary batteries.
By controlling the molar ratio of Fe(1+X)O(1+3/2X) to lithium dihydrogen phosphate in the lithium iron phosphate precursor material to 1:(1.03~1.2), adding 6% to 10% carbon source, and heat-treating under an inert gas atmosphere, lithium iron phosphate materials with high specific surface area and high compaction density are formed. Metal oxide dopants such as TiO2, MnO, ZnO, Al2O3, and V2O5 are introduced to optimize particle size and aggregation degree, forming a uniform pore structure.
It improves the electron and lithium-ion transport efficiency of lithium iron phosphate materials, enhances electrochemical activity and capacity, extends the service life of materials, and increases the energy density of lithium iron phosphate materials.
Smart Images

Figure CN120841475A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of secondary battery technology, specifically to lithium iron phosphate precursor materials and their preparation methods, lithium iron phosphate materials and their preparation methods, positive electrode sheets, and secondary batteries. Background Technology
[0002] Cathode materials are one of the core components of lithium-ion batteries. Commercially available cathode materials mainly include lithium cobalt oxide, lithium manganese oxide, nickel-cobalt-manganese ternary systems, and lithium iron phosphate. Materials containing cobalt and nickel offer high voltage, high capacity, and high volumetric energy density, but suffer from poor thermal stability, low thermal runaway temperature, and high oxygen release, which can easily lead to safety issues. They are generally limited to small batteries, such as those used in mobile phones, laptops, and power banks. Lithium manganese oxide materials are low-cost and safe, but have relatively low capacity and suffer from severe capacity degradation during high-temperature cycling. Lithium iron phosphate cathode materials, on the other hand, offer advantages such as a specific capacity of 170 mAh / g, a stable voltage platform of 3.4V, structural stability, excellent long-cycle performance, low cost, and safety (non-toxicity), making them a highly sought-after material. In recent years, lithium iron phosphate materials have seen significant development, particularly in the field of power batteries. However, due to the low intrinsic density (3.6 g / cc) and the capacity limit of 170 mAh / g, lithium iron phosphate materials have a large gap in energy density compared with ternary cathode materials, especially high-nickel ternary materials. Now, the market has increasingly higher requirements for the energy density of secondary batteries, so developing high-energy-density lithium iron phosphate materials is of great significance. Summary of the Invention
[0003] In view of the technical problems existing in the background art, this application provides a lithium iron phosphate precursor material and its preparation method, a lithium iron phosphate material and its preparation method, a positive electrode sheet and a secondary battery, aiming to solve the technical problem of low energy density of lithium iron phosphate materials.
[0004] In a first aspect, embodiments of this application provide a lithium iron phosphate precursor material, the lithium iron phosphate precursor material comprising Fe (1+X) O (1+3 / 2X) Lithium dihydrogen phosphate and the primary carbon source; Fe (1+X) O (1+3 / 2X) The molar ratio of divalent iron to lithium dihydrogen phosphate is 1:(1.03~1.2); X is less than or equal to 0.04; the carbon content of the first carbon source in the lithium iron phosphate precursor material is 6% to 10% by weight; the specific surface area of the lithium iron phosphate precursor material is 8m². 2 / g to 10m 2 / g, the compaction density under 3T pressure is 1.6g / mL to 2.5g / mL.
[0005] In the technical solution of this application, Fe in the lithium iron phosphate precursor material (1+X) O(1+3 / 2X) Using divalent iron as the source, lithium dihydrogen phosphate as the lithium source and phosphorus source, and controlling their molar ratio at 1:(1.03~1.2), the amount of carbon source was controlled, and the lithium iron phosphate precursor material possessed high compaction density and high specific surface area. Firstly, the addition of the carbon source and the control of its amount are beneficial for the formation of a conductive network and pore structure during subsequent heat treatment, improving the electron and lithium-ion transport efficiency of the prepared lithium iron phosphate and increasing the capacity of the lithium iron phosphate material. Secondly, a specific surface area of 10m² was used... 2 / g to 12m 2 A specific surface area of 10 m² / g for the lithium iron phosphate precursor material is beneficial for preparing lithium iron phosphate materials with high specific surface area, increasing the active sites, accelerating the electrochemical reaction rate, and improving the electrochemical activity and capacity of the lithium iron phosphate material. Furthermore, controlling the specific surface area of the lithium iron phosphate precursor material to 10 m² / g is advantageous. 2 / g to 12m 2 / g, with a compaction density of 1.6g / mL to 2.5g / mL, which is beneficial for subsequent heat treatment to obtain high-capacity, high-compact-density lithium iron phosphate materials, thereby improving the energy density of lithium iron phosphate materials. Furthermore, with Fe... (1+X) O (1+3 / 2X) Using lithium dihydrogen phosphate (LiH2PO4) as a source of divalent iron and lithium and phosphorus respectively, and controlling their molar ratio at 1:(1.03–1.2), while limiting the amount of trivalent iron (≤0.01), is beneficial for the complete lithiation of iron atoms. Furthermore, during the pyrolysis of the lithium iron phosphate precursor material to produce lithium iron phosphate material, LiH2PO4, as both a lithium and phosphorus source, reacts with the iron source to generate LiFePO4. Excess LiH2PO4 can promote the complete reaction, helping to avoid the formation of semi-finished products or byproducts, such as FePO4, and improving the purity, capacity, cycle performance, and other electrochemical properties of the lithium iron phosphate material. Simultaneously, excess lithium source promotes closer contact between particles within the prepared lithium iron phosphate material, increasing its compaction density.
[0006] In some embodiments, the lithium iron phosphate precursor material further comprises a metal oxide dopant, wherein the metal element in the metal oxide dopant is selected from one or more of Ti, Mn, Zn, Al, and V; Fe (1+X) O (1+3 / 2X) The ratio of the number of moles of divalent iron to the number of moles of metal element in the metal oxide dopant is 1:(0.001~0.008).
[0007] In this embodiment, the method involves doping the lithium iron phosphate precursor material with a small amount of metal oxide dopants (such as TiO2, MnO, ZnO, Al2O3, V2O5, etc.). This alters the crystal structure of the lithium iron phosphate material, introducing defects or forming solid solutions, thereby providing additional pathways for lithium-ion diffusion and reducing the transport resistance of lithium ions during charging and discharging. For example, the incorporation of Ti, Al, etc., can enhance the structural stability of the material, reduce volume changes during charging and discharging, and promote rapid lithium-ion transport by forming solid solution phases. This not only helps to increase the capacity of the lithium iron phosphate material but also helps to extend its service life. Furthermore, metal oxides facilitate the participation of more lithium ions in electrochemical reactions, improving lithium-ion utilization and thus increasing the theoretical capacity of the lithium iron phosphate material.
[0008] In some embodiments, the first carbon source is selected from one or more of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol, and / or the first carbon source is selected from one or more intermediate products obtained by heating and decomposition of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol.
[0009] In this embodiment, the carbonization of the carbon source during the heating and pyrolysis process not only constructs a conductive carbon network but also releases gas as a pore-forming agent, creating uniform pores within the lithium iron phosphate material. The presence of these pores increases the specific surface area of the lithium iron phosphate precursor material, providing more active sites for lithium ion adsorption and desorption, thereby improving the electrochemical activity and lithium storage capacity of the lithium iron phosphate material. The presence of pores also facilitates electrolyte penetration, ensuring rapid lithium ion transport within the material. Furthermore, the uniformly distributed pores ensure the uniformity and stability of the internal structure of the lithium iron phosphate precursor material, avoiding inconsistencies in electrochemical performance caused by excessive or insufficient local pores. Selecting the aforementioned carbon source and controlling its dosage as described above is beneficial for forming lithium iron phosphate materials with high conductivity and structural stability, thereby improving the energy density and other electrochemical properties of the lithium iron phosphate material.
[0010] In some embodiments, the D10 particle size of the lithium iron phosphate precursor material is 1 μm to 2 μm, the D50 particle size is 5 μm to 10 μm, the D90 particle size is 12 μm to 35 μm, and the aggregation index satisfies: 0.9 ≤ (D90-D10) / D50 ≤ 5.
[0011] In this embodiment, controlling the particle size and aggregation index of the lithium iron phosphate precursor material to be within the above-mentioned range is beneficial to the rapid transport of lithium ions in the prepared lithium iron phosphate material and reduces the agglomeration of the lithium iron phosphate material, and forms a lithium iron phosphate material with a more uniform particle size distribution, thereby improving the compaction density and capacity of the lithium iron phosphate material.
[0012] Secondly, embodiments of this application provide a method for preparing lithium iron phosphate precursor material, comprising the following steps: ball milling and dispersing a mixture containing ferrous oxalate, lithium dihydrogen phosphate, a second carbon source and a dispersion medium to obtain a slurry; spray drying the slurry to obtain a dried material; and heat-treating the dried material at 150°C to 400°C under an inert gas atmosphere to decompose the ferrous oxalate, thereby obtaining the lithium iron phosphate precursor material.
[0013] The molar ratio of divalent iron to lithium dihydrogen phosphate in ferrous oxalate is 1:(1.03~1.2).
[0014] The carbon content of the second carbon source in the dried material is 2% to 5% by weight.
[0015] The dispersion medium is selected from at least one of water, ethanol, ethanol, and propanol.
[0016] In the technical solution of this application embodiment, a uniform slurry is formed by ball milling and dispersing a mixture of ferrous oxalate, lithium dihydrogen phosphate, a second carbon source, and a dispersion medium. This slurry is then spray-dried to obtain a dried material with a high specific surface area and high fluidity, which is beneficial for heat treatment (150°C to 400°C) and the formation of a lithium iron phosphate precursor material with uniform composition and pore distribution. Furthermore, heat treatment of the dried material in an inert gas atmosphere (such as nitrogen or argon) within a temperature range of 150°C to 400°C facilitates the uniform decomposition of ferrous oxalate into iron oxide (Fe). (1+X) O (1+3 / 2X) The method involves in-situ formation of a lithium iron phosphate precursor material with a porous structure and relatively uniform pore distribution using CO and CO2 gases. By ball milling, spray drying, and thermal decomposition of a mixture of ferrous oxalate, lithium dihydrogen phosphate, a second carbon source, and a dispersion medium, and by controlling the amount of raw materials, the amount of carbon source added, and the heating conditions, a lithium iron phosphate precursor with high specific surface area and compaction density can be obtained. This is beneficial for the uniform reaction of iron, lithium, and phosphorus sources and the uniform carbonization of the carbon source in the lithium iron phosphate precursor material during subsequent lithium iron phosphate preparation. The prepared lithium iron phosphate material has both high capacity and high compaction density, thereby improving the capacity of the lithium iron phosphate material.
[0017] In some embodiments, the mixture further includes a metal element dopant, which is selected from one or more metal oxides and / or metal acetate salts selected from Ti, Mn, Zn, Al, and V, and the metal salt is selected from one or two of acetate or carbonate; in the mixture, the molar ratio of divalent iron in ferrous oxalate to metal element in the metal element dopant is 1:(0.001 to 0.008).
[0018] In this embodiment, the acetate is decomposed to generate ferrous oxide while simultaneously generating a corresponding metal oxide, which is then doped into the lithium iron phosphate precursor material. Alternatively, metal oxides can be directly used for doping into the lithium iron phosphate precursor material, which helps to improve the capacity of the subsequently prepared lithium iron phosphate material.
[0019] In some embodiments, the second carbon source is selected from one or more of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol.
[0020] In this embodiment, the carbon source or its thermal decomposition products (from 150°C to 400°C) are beneficial for carbonization during subsequent heat treatment to form a uniform conductive network and pore structure, thereby improving the electron and lithium-ion transport efficiency of the prepared lithium iron phosphate and increasing the capacity of the lithium iron phosphate material.
[0021] In some embodiments, the heat treatment temperature is 200°C to 300°C, and the heat treatment time is 2 hours to 10 hours.
[0022] Under the aforementioned temperature and heating time, it is beneficial for ferrous oxalate to decompose uniformly and form lithium iron phosphate precursor materials with more uniform pore distribution and stable structure. It can also reduce the formation of iron metal byproducts from further reduction of FeO and the formation of Fe3O4 and iron metal byproducts from further disproportionation of FeO, so as to obtain lithium iron phosphate precursors with higher purity and improve the electrochemical performance such as energy density of the subsequently prepared lithium iron phosphate.
[0023] In some embodiments, before heat treatment of the dried material, it is pretreated by heating at 40°C to 140°C for 2 to 12 hours to remove the water of crystallization from ferrous oxalate.
[0024] In this embodiment, the pretreatment can remove moisture and water of crystallization (e.g., water of crystallization in ferrous oxalate, water of crystallization in glucose) from the dried material and preliminarily solidify the material structure. This is beneficial to improving the efficiency of subsequent heat treatment at 150°C to 400°C and the purity of the product, as well as reducing the risk of material structure damage caused by moisture evaporation at high temperatures, so as to form a more stable lithium iron phosphate precursor material.
[0025] In some embodiments, the ferrous oxalate content in the slurry is 11% to 20% by weight.
[0026] In this embodiment, the ferrous oxalate content is within the above-mentioned range, which helps to form a uniform and stable slurry, so that subsequent spray drying of uniform and fine particles and heat treatment can form a dense and uniform lithium iron phosphate precursor material, thereby improving the compaction density, conductivity and lithium-ion transport efficiency of the subsequently prepared lithium iron phosphate material.
[0027] In some embodiments, the D50 particle size of the solid particles in the slurry is 260 nm to 400 nm.
[0028] In this embodiment, the D50 particle size of the solid particles in the slurry is within the above-mentioned range, which is beneficial to the rapid transport of lithium ions in the prepared lithium iron phosphate material and to obtaining lithium iron phosphate material with higher compaction density, thereby improving the energy density of lithium iron phosphate material.
[0029] In some embodiments, the ball mill rotation speed is 350 rpm to 450 rpm, and the ball milling time is 6 h to 10 h.
[0030] In this embodiment, under the above-mentioned ball milling conditions, the raw materials can be uniformly dispersed to form a uniform slurry, thereby improving the uniformity and performance consistency of the lithium iron phosphate precursor material.
[0031] It should be noted that the lithium dihydrogen phosphate used can be commercially available or prepared. In some embodiments, lithium dihydrogen phosphate is prepared from a lithium source and a phosphorus source. The preparation of lithium dihydrogen phosphate includes the following steps: dissolving the lithium source and the phosphorus source in water to obtain a first mixture, heating the first mixture at 60°C to 200°C to remove water, thereby obtaining lithium dihydrogen phosphate; the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium acetate, and the phosphorus source is selected from one or more of ammonium phosphate, monoammonium phosphate, and ammonium dihydrogen phosphate.
[0032] In this embodiment, the direct preparation using lithium and phosphorus sources is beneficial for cost savings. Furthermore, the use of lithium carbonate, lithium hydroxide, and lithium acetate as lithium sources, and ammonium phosphate, monoammonium phosphate, and ammonium dihydrogen phosphate as phosphorus sources, allows for the thorough removal of impurities such as ammonium ions and carbonate ions during the heating and water removal process. Therefore, using lithium dihydrogen phosphate prepared by this method as a raw material is beneficial for preparing high-purity lithium iron phosphate materials.
[0033] In some embodiments, the molar ratio of lithium in the lithium source to phosphorus in the phosphorus source is 1:1.01 to 1.05, which is beneficial for obtaining lithium dihydrogen phosphate with higher purity.
[0034] Thirdly, embodiments of this application provide a lithium iron phosphate material, which is prepared from the aforementioned lithium iron phosphate precursor material or from a lithium iron phosphate precursor material prepared by the aforementioned method for preparing lithium iron phosphate precursor material.
[0035] In some embodiments, the compaction density of the lithium iron phosphate material is from 2.64 g / mL to 3.0 g / mL.
[0036] In some embodiments, the initial discharge capacity of the lithium iron phosphate material is 155 mAh / g to 161 mAh / g.
[0037] In some embodiments, the initial coulombic efficiency of the lithium iron phosphate material is 97% to 99.8%.
[0038] In some embodiments, the powder internal resistance of the lithium iron phosphate material is from 4 Ω·cm to 10 Ω·cm.
[0039] Fourthly, embodiments of this application provide a method for preparing lithium iron phosphate material, comprising the following steps:
[0040] Under an inert gas atmosphere, the above-mentioned lithium iron phosphate precursor material or the lithium iron phosphate precursor material prepared by the above-mentioned method is calcined at 450°C to 800°C for 2 to 10 hours to obtain lithium iron phosphate material.
[0041] In this embodiment, the above heating conditions are beneficial to the Fe content in the lithium iron phosphate precursor material. (1+X) O (1+3 / 2X) The lithium iron phosphate is reacted with lithium dihydrogen phosphate to produce lithium iron phosphate and carbonized with a carbon source to obtain lithium iron phosphate material with high capacity and high compaction density.
[0042] In some embodiments, the calcination temperature is 700°C to 800°C.
[0043] The lithium iron phosphate precursor material has a high specific surface area, which is beneficial for uniform heating during heat treatment. In this embodiment, by using the above-mentioned high heat treatment temperature, the iron source, lithium source and phosphorus source in the lithium iron phosphate precursor material can be uniformly reacted and the carbon source can be uniformly carbonized, forming a lithium iron phosphate material with a uniform composition distribution. Furthermore, the above-mentioned high heat treatment temperature is conducive to the densification of the lithium iron phosphate material, thereby increasing the compaction density of the lithium iron phosphate material.
[0044] Fifthly, embodiments of this application provide a positive electrode sheet, which includes the above-mentioned lithium iron phosphate material, or the lithium iron phosphate material prepared by the above-mentioned method for preparing lithium iron phosphate precursor material.
[0045] In this embodiment, the positive electrode contains the aforementioned lithium iron phosphate material, thus having the advantage of high energy density.
[0046] Sixthly, embodiments of this application provide a secondary battery, including a positive electrode, wherein the positive electrode used is the aforementioned positive electrode sheet.
[0047] In this embodiment, the secondary battery includes the aforementioned positive electrode plate, thus having the advantage of high energy density.
[0048] In a seventh aspect, embodiments of this application provide an electrical device that includes the aforementioned secondary battery.
[0049] In this embodiment, the electrical device includes the aforementioned secondary battery, thus having the advantage of high energy density.
[0050] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0051] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0052] Figure 1 This is a schematic diagram of the vehicle structure in an embodiment of this application;
[0053] Figure 2 This is an exploded view of the battery in an embodiment of this application;
[0054] Figure 3 This is a SEM image of the lithium iron phosphate precursor material prepared in Example 1 of this application at the first magnification.
[0055] Figure 4 This is a SEM image of the lithium iron phosphate precursor material prepared in Example 1 of this application at a second magnification.
[0056] Figure 5 The XRD pattern of the dried material prepared in Example 1 of this application;
[0057] Figure 6 The image shows the XRD pattern of the lithium iron phosphate precursor material prepared in Example 1 of this application.
[0058] Figure 7 This is a SEM image of the composite lithium iron phosphate material prepared in Example 1 of this application;
[0059] Figure 8 SEM image of the lithium iron phosphate precursor material prepared for Comparative Example 1.
[0060] Explanation of reference numerals in the attached figures:
[0061] 1000. Electrical appliances;
[0062] 100. Battery; 10. Housing; 11. First part of the housing; 12. Second part of the housing; 20. Individual battery cell;
[0063] 200. Controller;
[0064] 300. Motor. Detailed Implementation
[0065] The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0066] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0067] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0068] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0069] In the description of the embodiments in this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, and B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship.
[0070] In the description of the embodiments of this application, the term "multiple" refers to two or more (including two), similarly, "multiple sets" refers to two or more (including two sets), and "multiple pieces" refers to two or more (including two pieces).
[0071] In the description of the embodiments of this application, the technical terms "center," "longitudinal," "lateral," "length," "width," "thickness," "upper," "lower," "front," "rear," "left," "right," "vertical," "horizontal," "top," "bottom," "inner," "outer," "clockwise," "counterclockwise," "axial," "radial," and "circumferential" indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings. They are only for the convenience of describing the embodiments of this application and simplifying the description, and are not intended to indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation. Therefore, they should not be construed as limitations on the embodiments of this application.
[0072] In the description of the embodiments of this application, unless otherwise expressly specified and limited, technical terms such as "installation," "connection," "joining," and "fixing" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral part; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; they can refer to the internal communication of two components or the interaction between two components. For those skilled in the art, the specific meaning of the above terms in the embodiments of this application can be understood according to the specific circumstances.
[0073] The existing technology suffers from the problem of low energy density in lithium iron phosphate materials. To address this issue, this application provides a lithium iron phosphate precursor material and its preparation method, a lithium iron phosphate material and its preparation method, a positive electrode sheet, and a secondary battery. The lithium iron phosphate precursor material in this application has a high compaction density and specific surface area, which facilitates the diffusion and transport of lithium ions in the lithium iron phosphate material obtained through subsequent heat treatment. This is beneficial for obtaining high-capacity, high-compact-density lithium iron phosphate materials, thereby improving the energy density of the lithium iron phosphate material, and consequently enhancing the energy density of the positive electrode sheet, the secondary battery, and the power device.
[0074] The electrical devices provided in this application embodiment can be, but are not limited to, mobile phones, tablets, laptops, electric toys, power tools, electric vehicles, electric cars, ships, spacecraft, etc. Among them, electric toys can include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc., and spacecraft can include airplanes, rockets, space shuttles, and spacecraft, etc.
[0075] For ease of explanation, the following embodiments will be described using a vehicle as an example of an electrical device 1000 according to an embodiment of this application.
[0076] Please refer to Figure 1 , Figure 1This is a schematic diagram of the structure of an electrical device 1000 provided in some embodiments of this application. The electrical device 1000 can be a gasoline-powered vehicle, a natural gas-powered vehicle, or a new energy vehicle. New energy vehicles can be pure electric vehicles, hybrid electric vehicles, or range-extended electric vehicles, etc. A battery 100 is internally disposed in the electrical device 1000, and the battery 1000 can be located at the bottom, head, or tail of the electrical device 1000. The battery 100 can be used to power the electrical device 1000; for example, the battery 100 can serve as the operating power source for the electrical device 1000. The electrical device 1000 may also include a controller 200 and a motor 300. The controller 200 is used to control the battery 100 to supply power to the motor 300, for example, to meet the power needs of the electrical device 1000 during startup, navigation, and driving.
[0077] In some embodiments of this application, the battery 100 can not only serve as the operating power source for the electrical device 1000, but also as the driving power source for the electrical device 1000, replacing or partially replacing fuel oil or natural gas to provide driving power for the electrical device 1000.
[0078] Please refer to Figure 2 , Figure 2 This is an exploded structural diagram of a battery according to some embodiments of this application. The battery 100 includes a housing 10 and a battery cell 20, with the battery cell 20 housed within the housing 10. The housing 10 provides a space for the battery cell 20 and can have various structures. In some embodiments, the housing 10 may include a first housing portion 11 and a second housing portion 12, which overlap each other, jointly defining a space for accommodating the battery cell 20. The second housing portion 12 may be a hollow structure with one open end, while the first housing portion 11 may be a plate-like structure, covering the open side of the second housing portion 12 so that the first housing portion 11 and the second housing portion 12 jointly define the space. Alternatively, both the first housing portion 11 and the second housing portion 12 may be hollow structures with one open side, with the open side of the first housing portion 11 covering the open side of the second housing portion 12. Of course, the box 10 formed by the first box 11 and the second box 12 can be in various shapes, such as a cylinder, a cuboid, etc.
[0079] In battery 100, there can be multiple battery cells 20, which can be connected in series, parallel, or a combination thereof. A combination thereof means that multiple battery cells 20 are connected in both series and parallel. Multiple battery cells 20 can be directly connected in series, parallel, or a combination thereof, and then the entire assembly of the multiple battery cells 20 is housed within the casing 10. Alternatively, battery 100 can also consist of multiple battery cells 20 first connected in series, parallel, or a combination thereof to form a whole, and then housed within the casing 10. Battery 100 may also include other structures; for example, battery 100 may also include a busbar component for realizing the electrical connection between multiple battery cells 20.
[0080] Each battery cell 20 can be a secondary battery or a primary battery. The battery cell 20 can be cylindrical, flat, cuboid, or other shapes.
[0081] In a first aspect, embodiments of this application provide a lithium iron phosphate precursor material, the lithium iron phosphate precursor material comprising Fe (1+X) O (1+3 / 2X) Lithium dihydrogen phosphate and the primary carbon source; Fe (1+X) O (1+3 / 2X) The molar ratio of divalent iron to lithium dihydrogen phosphate is 1:(1.03~1.2); X is less than or equal to 0.04; the carbon content of the first carbon source in the lithium iron phosphate precursor material is 6% to 10% by weight; the specific surface area of the lithium iron phosphate precursor material is 8m². 2 / g to 10m 2 / g, the compaction density under 3T pressure is 1.6g / mL to 2.5g / mL.
[0082] In the technical solution of this application embodiment, Fe in the lithium iron phosphate precursor material (1+X) O (1+3 / 2X) Using divalent iron as the source, lithium dihydrogen phosphate as the lithium source and phosphorus source, and controlling their molar ratio at 1:(1.03~1.2), the amount of carbon source was controlled, and the lithium iron phosphate precursor material possessed high compaction density and high specific surface area. Firstly, the addition of the carbon source and the control of its amount are beneficial for the formation of a conductive network and pore structure during subsequent heat treatment, improving the electron and lithium-ion transport efficiency of the prepared lithium iron phosphate and increasing the capacity of the lithium iron phosphate material. Secondly, a specific surface area of 10m² was used... 2 / g to 12m 2 A specific surface area of 10 m² / g of lithium iron phosphate precursor material is beneficial for preparing lithium iron phosphate materials with high specific surface area, increasing the active sites of lithium iron phosphate materials, accelerating the electrochemical reaction rate, and improving the electrochemical activity and capacity of lithium iron phosphate materials. Meanwhile, a specific surface area of 10 m² / g is also advantageous. 2 / g to 12m 2The specific surface area and compaction density of the lithium iron phosphate precursor material are within the range of 1.6 g / mL to 2.5 g / mL, which is beneficial for subsequent heat treatment to obtain high-capacity, high-compaction-density lithium iron phosphate material and improve the energy density of the lithium iron phosphate material. Furthermore, it facilitates the uniform reaction of iron, lithium, and phosphorus sources in the lithium iron phosphate precursor material and the uniform carbonization of the carbon source during subsequent heat treatment, further forming a lithium iron phosphate material with a uniform composition distribution. The prepared lithium iron phosphate material has both high capacity and high compaction density. Moreover, with Fe... (1+X) O (1+3 / 2X) Using lithium dihydrogen phosphate (LiH2PO4) as a source of divalent iron and lithium and phosphorus respectively, and controlling their molar ratio at 1:(1.03–1.2), while limiting the amount of trivalent iron (≤0.01), is beneficial for the complete lithiation of iron atoms. Furthermore, during the pyrolysis of the lithium iron phosphate precursor material to produce lithium iron phosphate material, LiH2PO4, as both a lithium and phosphorus source, reacts with the iron source to generate LiFePO4. Excess LiH2PO4 can promote the complete reaction, helping to avoid the formation of semi-finished products or byproducts, such as FePO4, and improving the purity, capacity, cycle performance, and other electrochemical properties of the lithium iron phosphate material. Simultaneously, excess lithium source promotes closer contact between particles within the prepared lithium iron phosphate material, increasing its compaction density.
[0083] Furthermore, in some embodiments, the lithium iron phosphate precursor material further comprises a metal oxide dopant, wherein the metal element in the metal oxide dopant is selected from one or more of Ti, Mn, Zn, Al, and V; Fe (1+X) O (1+3 / 2X) The ratio of the number of moles of divalent iron to the number of moles of metal elements in the metal oxide dopant is 1:(0.001~0.008).
[0084] In the technical solution of this application embodiment, the method involves introducing a small amount of metal oxide dopants (such as TiO2, MnCO3, ZnO, Al2O3, V2O5, etc.) into the lithium iron phosphate precursor material. This doping helps to change the crystal structure of the lithium iron phosphate material, introduce defects, or form solid solutions, thereby providing additional pathways for lithium-ion diffusion and reducing the transport resistance of lithium ions during charging and discharging. For example, the incorporation of Ti, Al, etc., can enhance the structural stability of the material, reduce the volume change of the material during charging and discharging, and promote the rapid transport of lithium ions by forming solid solution phases. This not only helps to improve the capacity of the lithium iron phosphate material but also helps to extend its service life. In addition, metal oxides facilitate the participation of more lithium ions in electrochemical reactions, improve the utilization rate of lithium ions, and thus increase the theoretical capacity of the lithium iron phosphate material.
[0085] Furthermore, in some embodiments, the first carbon source is selected from one or more of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol, and / or the first carbon source is selected from one or more intermediate products obtained by heating and decomposition of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol.
[0086] In this embodiment, the carbonization of the carbon source during the heating and pyrolysis process can not only construct a conductive carbon network, but also release gas as a pore-forming agent to form uniform pores inside the lithium iron phosphate material. By selecting the above-mentioned carbon source and controlling the dosage as described above, it is beneficial to form a lithium iron phosphate material with high conductivity and structural stability and uniform pore distribution, thereby improving the electrochemical performance of the lithium iron phosphate material, such as energy density.
[0087] Furthermore, in some embodiments, the D10 particle size of the lithium iron phosphate precursor material is 1 μm to 2 μm, the D50 particle size is 5 μm to 10 μm, the D90 particle size is 12 μm to 35 μm, and the aggregation index satisfies: 0.9 ≤ (D90-D10) / D50 ≤ 5.
[0088] In this embodiment, controlling the particle size and aggregation index of the lithium iron phosphate precursor material to be within the above-mentioned range is beneficial to the rapid transport of lithium ions in the prepared lithium iron phosphate material and reduces the agglomeration of the lithium iron phosphate material, and forms a lithium iron phosphate material with a more uniform particle size distribution, thereby improving the compaction density and capacity of the lithium iron phosphate material.
[0089] Secondly, embodiments of this application provide a method for preparing a lithium iron phosphate precursor material, comprising the following steps: ball milling and dispersing a mixture containing ferrous oxalate, lithium dihydrogen phosphate, a second carbon source, and a dispersion medium to obtain a slurry; spray drying the slurry to obtain a dried material; and heat-treating the dried material at 150°C to 400°C under an inert gas atmosphere to decompose the ferrous oxalate, thereby obtaining the lithium iron phosphate precursor material; wherein, the molar ratio of divalent iron to lithium dihydrogen phosphate in ferrous oxalate is 1:(1.03~1.2); the carbon content of the second carbon source in the dried material is 2% to 5% by weight; and the dispersion medium is selected from at least one of water, ethanol, ethanol, and propanol.
[0090] In the technical solution of this application embodiment, a uniform slurry is formed by ball milling and dispersing a mixture of ferrous oxalate, lithium dihydrogen phosphate, a second carbon source, and a dispersion medium. This slurry is then spray-dried to obtain a dried material with a high specific surface area and high fluidity, which is beneficial for heat treatment (150°C to 400°C) and the formation of a lithium iron phosphate precursor material with a uniform composition distribution. Furthermore, heat-treating the dried material in an inert gas atmosphere (such as nitrogen or argon) within a temperature range of 150°C to 400°C facilitates the uniform decomposition of ferrous oxalate into iron oxide (Fe). (1+X) O(1+3 / 2X) The method involves in-situ formation of a lithium iron phosphate precursor material with a porous structure and relatively uniform pore distribution using CO and CO2 gases. Using the method described in this application, a mixture of ferrous oxalate, lithium dihydrogen phosphate, a second carbon source, and a dispersion medium is ball-milled, spray-dried, and thermally decomposed. By controlling the amount of raw materials, the amount of carbon source added, and the heating conditions, a lithium iron phosphate precursor with high specific surface area and compaction density can be obtained. This is beneficial for the uniform reaction of iron, lithium, and phosphorus sources in the lithium iron phosphate precursor material and the uniform carbonization of the carbon source during subsequent lithium iron phosphate preparation. The prepared lithium iron phosphate material has both high capacity and high compaction density, thereby improving the capacity of the lithium iron phosphate material.
[0091] Furthermore, in some embodiments, the mixture further includes a metal element dopant, which is selected from one or more metal oxides and / or metal salts selected from Ti, Mn, Zn, Al, and V, and the metal salt is selected from one or two acetates or carbonates; in the mixture, the molar ratio of divalent iron in ferrous oxalate to metal element in the metal element dopant is 1:(0.001 to 0.008).
[0092] In the technical solution of this application embodiment, the above-mentioned acetate is decomposed to generate ferrous oxide while ferrous acetate is decomposed to generate corresponding metal oxides for doping into the lithium iron phosphate precursor material, or metal oxides are directly used for doping into the lithium iron phosphate precursor material, which helps to improve the capacity of the subsequently prepared lithium iron phosphate material.
[0093] Furthermore, in some embodiments, the second carbon source is selected from one or more of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol.
[0094] In the technical solution of this application embodiment, the above-mentioned carbon source or its thermal decomposition products (150°C to 400°C) are beneficial to the formation of a uniform conductive network and pore structure during subsequent heat treatment, thereby improving the electron and lithium-ion transport efficiency of the prepared lithium iron phosphate and increasing the capacity of the lithium iron phosphate material.
[0095] Furthermore, in some embodiments, the heat treatment temperature is 200°C to 300°C, and the heat treatment time is 2 hours to 10 hours.
[0096] In the technical solution of this application embodiment, under the above-mentioned temperature and heating time, it is beneficial to uniformly decompose ferrous oxalate to form a structurally stable lithium iron phosphate precursor material, and can reduce the generation of iron metal element byproducts by further reduction of FeO and the generation of Fe3O4 and iron metal element byproducts by further disproportionation of FeO, so as to obtain a higher purity lithium iron phosphate precursor and improve the electrochemical performance such as energy density of the subsequently prepared lithium iron phosphate.
[0097] Furthermore, in some embodiments, before heat treatment of the dried material, it is pretreated by heating at 40°C to 140°C for 2 to 12 hours to remove the water of crystallization from ferrous oxalate.
[0098] In the technical solution of this application embodiment, the pretreatment can remove moisture and water of crystallization (e.g., water of crystallization in ferrous oxalate, water of crystallization in glucose) from the dried material and preliminarily solidify the material structure, which is beneficial to improve the efficiency of subsequent heat treatment from 150°C to 400°C and the purity of the product, as well as reduce the risk of material structure damage caused by moisture evaporation at high temperature, so as to form a more stable lithium iron phosphate precursor material.
[0099] Furthermore, in some embodiments, the ferrous oxalate content in the slurry is 11% to 20% by weight.
[0100] In the technical solution of this application embodiment, the ferrous oxalate content is within the above-mentioned range, which helps to form a uniform and stable slurry, so that the subsequent spray drying of uniform and fine particles and heat treatment can form a dense and uniform lithium iron phosphate precursor material, thereby improving the compaction density, conductivity and lithium ion transport efficiency of the subsequently prepared lithium iron phosphate material.
[0101] Furthermore, in some embodiments, the D50 particle size of the solid particles in the slurry is 260 nm to 400 nm.
[0102] In the technical solution of this application embodiment, the D50 particle size of the solid particles in the slurry is within the above-mentioned range, which is beneficial to the rapid transport of lithium ions in the prepared lithium iron phosphate material and to obtain lithium iron phosphate material with higher compaction density, thereby improving the energy density of lithium iron phosphate material.
[0103] Furthermore, in some embodiments, the ball milling speed is 350 rpm to 450 rpm, and the ball milling time is 6 h to 10 h.
[0104] In the technical solution of this application embodiment, under the above-mentioned ball milling conditions, the raw materials can be uniformly dispersed to form a uniform slurry, thereby improving the uniformity and performance consistency of the lithium iron phosphate precursor material.
[0105] Lithium dihydrogen phosphate can be commercially available or prepared. In some embodiments, lithium dihydrogen phosphate is prepared from a lithium source and a phosphorus source. The preparation of lithium dihydrogen phosphate includes the following steps: dissolving the lithium source and the phosphorus source in water to obtain a first mixture, and heating the first mixture at 60°C to 200°C to remove water, thereby obtaining lithium dihydrogen phosphate; the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium acetate, and the phosphorus source is selected from one or more of ammonium phosphate, monoammonium phosphate, and ammonium dihydrogen phosphate.
[0106] In the technical solution of this application embodiment, the direct preparation using lithium and phosphorus sources is beneficial to saving costs. Furthermore, using lithium carbonate, lithium hydroxide, and lithium acetate as lithium sources and ammonium phosphate, monoammonium phosphate, and ammonium dihydrogen phosphate as phosphorus sources can fully remove impurities such as ammonium ions and carbonate ions during the heating and water removal process. Therefore, using lithium dihydrogen phosphate prepared by this method as raw material is beneficial to preparing high-purity lithium iron phosphate materials.
[0107] Furthermore, in some embodiments, the molar ratio of lithium in the lithium source to phosphorus in the phosphorus source is 1:1.01 to 1.05, which is beneficial for obtaining lithium dihydrogen phosphate with higher purity.
[0108] Thirdly, embodiments of this application provide a lithium iron phosphate material, which is prepared from the aforementioned lithium iron phosphate precursor material or from a lithium iron phosphate precursor material prepared by the aforementioned method for preparing lithium iron phosphate precursor material.
[0109] Furthermore, in some embodiments, the compaction density of the lithium iron phosphate material is from 2.64 g / mL to 3.0 g / mL.
[0110] Furthermore, in some embodiments, the initial discharge capacity of the lithium iron phosphate material is 155 mAh / g to 161 mAh / g.
[0111] Furthermore, in some embodiments, the initial coulombic efficiency of the lithium iron phosphate material is 97% to 99.8%.
[0112] Furthermore, in some embodiments, the internal resistance of the lithium iron phosphate material powder is from 4 Ω·cm to 12 Ω·cm.
[0113] Fourthly, embodiments of this application provide a method for preparing lithium iron phosphate material, comprising the following steps:
[0114] Under an inert gas atmosphere, the above-mentioned lithium iron phosphate precursor material or the lithium iron phosphate precursor material prepared by the above-mentioned method is calcined at 450°C to 800°C for 2 to 10 hours to obtain lithium iron phosphate material.
[0115] In the technical solution of this application embodiment, the above-mentioned heating conditions are beneficial to the Fe content in the lithium iron phosphate precursor material. (1+X) O (1+3 / 2X) The lithium iron phosphate is reacted with lithium dihydrogen phosphate to produce lithium iron phosphate and carbonized with a carbon source to obtain lithium iron phosphate material with high capacity and high compaction density.
[0116] Furthermore, in some embodiments, the calcination temperature is 700°C to 800°C.
[0117] Lithium iron phosphate precursor materials have high specific surface area and compaction density, which is beneficial for uniform heating during heat treatment. In the technical solution of this application embodiment, the above-mentioned high heat treatment temperature can achieve uniform reaction of iron source, lithium source and phosphorus source in lithium iron phosphate precursor material and uniform carbonization of carbon source, and form lithium iron phosphate material with uniform composition distribution. Furthermore, the above-mentioned high heat treatment temperature is conducive to densification of iron phosphate material, thereby improving the compaction density of iron phosphate material.
[0118] Fifthly, embodiments of this application provide a positive electrode sheet comprising the aforementioned lithium iron phosphate material, or a lithium iron phosphate material prepared by the aforementioned method for preparing a lithium iron phosphate precursor material. The positive electrode sheet comprising the aforementioned lithium iron phosphate material thus possesses the advantage of high energy density.
[0119] Sixthly, embodiments of this application provide a secondary battery including a positive electrode, wherein the positive electrode is the aforementioned positive electrode sheet. The secondary battery, containing the aforementioned positive electrode sheet, thus has the advantage of high energy density.
[0120] Seventhly, embodiments of this application provide an electrical device, such as a vehicle 1000, including the battery 100 as described in the above embodiments. The electrical device, comprising the aforementioned secondary battery, thus has the advantage of high energy density.
[0121] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0122] I. Preparation Method
[0123] Example 1
[0124] Step 1: Ferrous oxalate dihydrate (FeC2O4·2H2O, wherein the weight percentage of ferric iron is 0.05%), lithium dihydrogen phosphate (Baijierui, purity 99.54%), glucose, and water are mixed to obtain a mixture. The mixture is ball-milled at 400 rpm for 8 hours to obtain a slurry. The slurry is then spray-dried to obtain a dried material. Specifically, the molar ratio of ferric iron to lithium dihydrogen phosphate in ferrous oxalate dihydrate is 1:1.1; the amount of carbon added in glucose is 3% (based on 100% weight of the dried material); the ferrous oxalate content in the slurry is 12% (by weight percentage); the D50 particle size of the solid particles in the slurry is 360 nm; and the D50 particle size of the dried material is 11 μm.
[0125] Step 2: Under a nitrogen atmosphere, the dried material is pretreated by heating at 120°C for 4 hours to remove the water of crystallization in ferrous oxalate, and then heat-treated at 250°C for 6 hours to decompose the ferrous oxalate, thus obtaining the lithium iron phosphate precursor material.
[0126] The SEM results of the lithium iron phosphate precursor material prepared in Example 1 are as follows: Figure 3 and Figure 4 As shown, by Figure 3 and Figure 4 It can be seen that the lithium iron phosphate precursor material has abundant pores and a uniform pore structure. The XRD results of the dried material are as follows: Figure 5 As shown, by Figure 5 It can be seen that the dried material contains ferrous oxalate dihydrate and lithium dihydrogen phosphate phases. The XRD results of the lithium iron phosphate precursor material are as follows: Figure 6 As shown, the lithium iron phosphate precursor material contains ferrous oxide phase and lithium dihydrogen phosphate phase, and has no obvious impurity peaks. Under nitrogen atmosphere, ferrous oxalate decomposes to generate ferrous oxide, and lithium dihydrogen phosphate does not decompose at this temperature.
[0127] Example 2
[0128] Step 1: Ferrous oxalate dihydrate (FeC2O4·2H2O, wherein the weight percentage of ferric iron is 0.05%), lithium dihydrogen phosphate, starch, and water are mixed to obtain a mixture. The mixture is ball-milled at 350 rpm for 6 hours to obtain a slurry. The slurry is then spray-dried to obtain a dried material. Specifically, the molar ratio of ferric iron to lithium dihydrogen phosphate in ferrous oxalate dihydrate is 1:1.03; the amount of carbon added from glucose is 4% (based on 100% weight of the dried material); the ferrous oxalate content in the slurry is 15% (by weight percentage); the D50 particle size of the solid particles in the slurry is 320 nm; and the D50 particle size of the dried material is 7 μm.
[0129] Step 2: Under a nitrogen atmosphere, the dried material is pretreated by heating at 130°C for 12 hours to remove the water of crystallization in ferrous oxalate, and then heat-treated at 150°C for 2 hours to decompose the ferrous oxalate, thus obtaining the lithium iron phosphate precursor material.
[0130] Example 3
[0131] Step 1: Ferrous oxalate dihydrate (FeC2O4·2H2O, wherein the weight percentage of ferric iron is 0.08%), lithium dihydrogen phosphate, polyethylene, and ethanol are mixed to obtain a mixture. The mixture is ball-milled at 450 rpm for 10 hours to obtain a slurry. The slurry is then spray-dried to obtain a dried material. Specifically, the molar ratio of ferric iron to lithium dihydrogen phosphate in ferrous oxalate dihydrate is 1:1.2; the amount of carbon added from glucose is 2% (based on 100% weight of the dried material); the ferrous oxalate content in the slurry is 15% (by weight percentage); the D50 particle size of the solid particles in the slurry is 300 nm; and the D50 particle size of the dried material is 7.5 μm.
[0132] Step 2: Under a nitrogen atmosphere, the dried material is pretreated by heating at 120°C for 2 hours to remove the water of crystallization in ferrous oxalate, and then heat-treated at 450°C for 10 hours to decompose the ferrous oxalate, thus obtaining the lithium iron phosphate precursor material.
[0133] Example 4
[0134] The only difference between it and Example 1 is that the amount of ferrous oxalate dihydrate is reduced, so that the molar ratio of divalent iron to lithium dihydrogen phosphate in ferrous oxalate dihydrate is 1:1.03.
[0135] Example 5
[0136] The only difference between it and Example 1 is that the amount of ferrous oxalate dihydrate is increased so that the molar ratio of divalent iron to lithium dihydrogen phosphate in ferrous oxalate dihydrate is 1:1.2.
[0137] Example 6
[0138] The only difference between it and Example 1 is that in step one, the amount of glucose is increased, and the amount of carbon in the glucose is added as 5% based on 100% of the weight of the dried material.
[0139] Example 7
[0140] The only difference between it and Example 1 is that the heat treatment temperature in step two is 300°C.
[0141] Example 8
[0142] The only difference between it and Example 1 is that the heat treatment temperature in step two is 400°C.
[0143] Example 9
[0144] The only difference between this and Example 1 is that no pretreatment was performed to remove the water of crystallization from ferrous oxalate before the heat treatment in step two.
[0145] Example 10
[0146] The only difference between this and Example 1 is that lithium dihydrogen phosphate is prepared from lithium and phosphorus sources. The preparation of lithium dihydrogen phosphate includes the following steps: weighing lithium carbonate and ammonium dihydrogen phosphate according to a molar ratio of lithium carbonate to ammonium dihydrogen phosphate of 1:2.05, dissolving lithium carbonate and ammonium dihydrogen phosphate in water to obtain a first mixture, and heating the first mixture at 120°C to remove water to obtain lithium dihydrogen phosphate; wherein, the concentration of lithium carbonate in the first mixture is 100 g / L.
[0147] Example 11
[0148] The only difference between this and Example 1 is that, in step one, titanium acetate is added to the mixture; in the mixture, the molar ratio of divalent iron in ferrous oxalate dihydrate to titanium in titanium acetate is 1:0.005.
[0149] Comparative Example 1
[0150] The only difference between this and Example 1 is that the amount of ferrous oxalate dihydrate is reduced in step one, so that the molar ratio of divalent iron to lithium dihydrogen phosphate in ferrous oxalate dihydrate is 1:1.
[0151] SEM images of the lithium iron phosphate precursor material prepared in Comparative Example 1 are shown below. Figure 8 As shown.
[0152] Comparative Example 2
[0153] The only difference between this and Example 1 is that the amount of ferrous oxalate dihydrate is increased in step one, so that the molar ratio of divalent iron to lithium dihydrogen phosphate in ferrous oxalate dihydrate is 1:1.3.
[0154] Comparative Example 3
[0155] The only difference between it and Example 1 is that in step one, the amount of glucose is increased, and the amount of carbon in the glucose is added as 8% based on the weight of the dried material as 100%.
[0156] Comparative Example 4
[0157] The only difference between it and Example 1 is that the heat treatment temperature in step two is 500°C.
[0158] Application Example 1
[0159] Under nitrogen protection, the lithium iron phosphate precursor material prepared in Example 1 was calcined at 750°C for 6 hours. After calcination, the calcined material was cooled to 100°C and discharged. The discharged material was then pulverized until the D50 particle size was 1.1 μm. Iron was removed and the material was packaged in a constant temperature and humidity chamber (temperature 25°C, humidity 9%) to obtain the lithium iron phosphate material.
[0160] The SEM results of the lithium iron phosphate material prepared in Example 1 are as follows: Figure 7 As shown, lithium iron phosphate materials have abundant pores, and the primary particles are uniform in size with a particle size of about 1.1 μm.
[0161] Application Examples 2 to 11
[0162] The only difference between this example and Example 1 is that the lithium iron phosphate precursor material used is the precursor material prepared in Examples 2 to 11.
[0163] Application of comparative examples 1 to 4
[0164] The only difference between this example and Application Example 1 is that the lithium iron phosphate precursor material used is the precursor material prepared in Comparative Examples 1 to 4.
[0165] II. Testing Methods
[0166] 1. Material property testing
[0167] 1) The morphology of the lithium iron phosphate precursor was characterized by scanning electron microscopy (SEM).
[0168] 2) The composition of lithium iron phosphate precursor was characterized using X-ray diffraction.
[0169] 3) The specific surface area of the material was tested using the nitrogen adsorption BET test method, referring to the standard GB / T9587-2017. The test results of the specific surface area of the lithium iron phosphate precursor material and the specific surface area of lithium iron phosphate prepared in the examples and comparative examples are shown in Table 1.
[0170] 4) The D10 particle size (nm), D50 particle size (nm), D90 particle size (nm), and particle size distribution (D90-D10) / D50 of the lithium iron phosphate precursor were measured using a laser particle size analyzer and are shown in Table 1.
[0171] 5) The compaction density of the materials under 3T pressure was tested using a JZ-1 powder compaction density tester. The compaction densities of the lithium iron phosphate precursor material and the lithium iron phosphate material are shown in Table 1.
[0172] 6) The elemental composition of the material was analyzed using inductively coupled plasma atomic emission spectrometry. The elemental contents of the lithium iron phosphate precursor material are shown in Table 2.
[0173] 2. Properties of secondary batteries
[0174] 1) Battery assembly
[0175] The lithium iron phosphate material prepared in the examples and comparative examples was mixed with conductive carbon powder and PVDF binder at a mass ratio of 90:5:5. After homogenization, the mixture was coated onto aluminum foil, dried at 100°C, rolled with a roller press, and then a positive electrode sheet with a diameter of 14 mm was obtained by a stamping machine.
[0176] After drying the positive electrode, the lithium sheet is used as the negative electrode. The CR2032 button cell is assembled in the following order: negative electrode shell, lithium sheet, electrolyte, separator, electrolyte, positive electrode, gasket, spring, and positive electrode shell, in a UNlab type inert gas glove box of Braun GmbH, Germany.
[0177] 2) Electrical performance testing
[0178] The electrochemical performance of CR2032 coin cells was tested using the Wuhan Landian CT2001A battery testing system. The voltage range was 2V to 4.55V, and the test temperature was 25℃. The results of the 0.1C initial charge capacity, 0.1C initial discharge capacity, and 0.1C initial coulombic efficiency are shown in Table 2.
[0179] III. Analysis of Test Results for Each Embodiment and Comparative Example
[0180] Table 1
[0181]
[0182]
[0183] Table 2
[0184]
[0185] As can be seen from the data in Tables 1 and 2, the lithium iron phosphate precursor materials prepared in Examples 1 to 11 of this application have high specific surface area, high compaction density, and low trivalent iron content. The lithium iron phosphate materials prepared using these precursor materials exhibit high specific surface area, high compaction density, and low powder internal resistance. Compared to Comparative Examples 1 to 4, the lithium iron phosphate materials prepared using the lithium iron phosphate precursor materials in Examples 1 to 11 show significantly increased initial charge capacity, initial charge capacity, and coulombic efficiency, and the lithium iron phosphate materials possess high energy density.
[0186] As can be seen from the comparison between the examples and Comparative Example 1, compared with Example 1 (iron-phosphorus molar ratio 1:1.1), Example 4 (1:1.03) and Example 5 (1:1.2), Comparative Example 1 (1:1.0) uses a lower amount of ferrous oxalate, and the lithium iron phosphate precursor material prepared has a lower specific surface area and a higher compaction density. The lithium iron phosphate material prepared using it has a lower compaction density and a higher powder internal resistance, and the initial charge capacity, initial charge capacity and coulombic efficiency are significantly reduced.
[0187] As can be seen from the comparison between the examples and Comparative Example 2, compared with Example 1 (iron-phosphorus molar ratio 1:1.1), Example 4 (1:1.03) and Example 5 (1:1.2), Comparative Example 2 (1:1.3) uses a higher amount of ferrous oxalate, and the lithium iron phosphate precursor material prepared has a higher specific surface area and a lower compaction density. The lithium iron phosphate material prepared using it has a lower compaction density, and the initial charge capacity, initial charge capacity and coulombic efficiency are significantly reduced.
[0188] As can be seen from the comparison between Examples 1 and 6 and Comparative Example 3, compared with Examples 1 (carbon content of 3%) and 6 (carbon content of 5%), Comparative Example 3 uses a higher amount of carbon source (carbon content of 8%), and the prepared lithium iron phosphate precursor material has a higher specific surface area and a lower compaction density. The lithium iron phosphate material prepared using it has a low compaction density, and the initial charge capacity, initial charge capacity and coulombic efficiency are significantly reduced.
[0189] The test results from Examples 1, 7, 8, and Comparative Example 4 show that, compared to Example 1 (250℃), Examples 7 (300℃) and 8 (400℃) used higher heat treatment temperatures, resulting in increased compaction density of the prepared lithium iron phosphate precursor materials. However, the powder internal resistance of the lithium iron phosphate materials prepared using these temperatures also increased. Furthermore, the initial charge capacity, initial charge capacity, and coulombic efficiency of the prepared lithium iron phosphate materials were also reduced. Further, when using an even higher heat treatment temperature as in Comparative Example 4 (500℃), the excessively high temperature caused material shrinkage and densification. Although the compaction density of the prepared lithium iron phosphate precursor material was further improved, the specific surface area was significantly reduced. The compaction density of the lithium iron phosphate materials prepared using this precursor material was also reduced, while the powder internal resistance increased. Simultaneously, the initial charge capacity, initial charge capacity, and coulombic efficiency were all significantly affected and reduced.
[0190] A comparison of Examples 1 and 9 shows that, compared to Example 9, the pretreatment in Example 1 to remove the water of crystallization from ferrous oxalate is more conducive to obtaining a lithium iron phosphate precursor with high purity and stable structure. It is evident that the specific surface area of the lithium iron phosphate precursor material prepared in Example 1 is greater than that prepared in Example 9. When the lithium iron phosphate precursor materials prepared in Examples 1 and 9 are used to prepare lithium iron phosphate materials, the compaction density of the lithium iron phosphate prepared using the lithium iron phosphate precursor material in Example 1 is significantly higher. The compaction density of lithium iron phosphate prepared from the lithium iron phosphate precursor material in Application Example 9 is higher than that of lithium iron phosphate prepared from the lithium iron phosphate precursor material in Application Example 1, and the powder internal resistance of lithium iron phosphate prepared from the lithium iron phosphate precursor material in Application Example 9 is lower than that of lithium iron phosphate prepared from the lithium iron phosphate precursor material in Application Example 9. As a result, the initial charge capacity, initial charge capacity, and coulombic efficiency of lithium iron phosphate prepared from the lithium iron phosphate precursor material in Application Example 1 are all higher than those of lithium iron phosphate prepared from the lithium iron phosphate precursor material in Application Example 9.
[0191] A comparison between Example 1 and Example 11 shows that, compared to Example 1, Example 11 involves titanium doping, and the prepared lithium iron phosphate precursor material contains the dopant element titanium. The lithium iron phosphate material prepared using this material has better rate performance. At the same time, because the internal ion channels are opened, the lithium ion diffusion distance is shortened, and the kinetic performance is also better.
[0192] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A lithium iron phosphate precursor material, characterized in that, The lithium iron phosphate precursor material contains Fe (1+X) O (1+3 / 2X) Lithium dihydrogen phosphate and a first carbon source; the Fe (1+X) O (1+3 / 2X) The molar ratio of divalent iron to lithium dihydrogen phosphate is 1:(1.03~1.2); X is less than or equal to 0.04; the carbon content of the first carbon source in the lithium iron phosphate precursor material is 6% to 10% by weight; the specific surface area of the lithium iron phosphate precursor material is 8m². 2 / g to 10m 2 / g, the compaction density under 3T pressure is 1.6g / mL to 2.5g / mL.
2. The lithium iron phosphate precursor material according to claim 1, characterized in that, The lithium iron phosphate precursor material further comprises a metal oxide dopant, wherein the metal element in the metal oxide dopant is selected from one or more of Ti, Mn, Zn, Al, and V; the Fe (1+X) O (1+3 / 2X) The molar ratio of divalent iron to the metal element in the metal oxide dopant is 1:(0.001~0.008).
3. The lithium iron phosphate precursor material according to claim 1, characterized in that, The first carbon source is selected from one or more of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol; and / or, the first carbon source is selected from one or more intermediate products obtained by heating and decomposition of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol.
4. The lithium iron phosphate precursor material according to any one of claims 1 to 3, characterized in that, The lithium iron phosphate precursor material has a D10 particle size of 1 μm to 2 μm, a D50 particle size of 5 μm to 10 μm, and a D90 particle size of 12 μm to 35 μm, and the aggregation index satisfies: 0.9 ≤ (D90-D10) / D50 ≤ 5.
5. A method for preparing a lithium iron phosphate precursor material, characterized in that, The process includes the following steps: ball milling and dispersing a mixture containing ferrous oxalate, lithium dihydrogen phosphate, a second carbon source, and a dispersion medium to obtain a slurry; spray drying the slurry to obtain a dried material; and heat-treating the dried material at 150°C to 400°C under an inert gas atmosphere to decompose the ferrous oxalate, thereby obtaining the lithium iron phosphate precursor material. The molar ratio of divalent iron in ferrous oxalate to lithium dihydrogen phosphate is 1:(1.03-1.2). The carbon content of the second carbon source in the dried material is 2% to 5% by weight. The dispersion medium is selected from at least one of water, ethanol, ethanol, and propanol.
6. The method for preparing lithium iron phosphate precursor material according to claim 5, characterized in that, The method for preparing the lithium iron phosphate precursor material has at least one of the following technical features: (1) The mixture further includes a metal element dopant, which is selected from one or more metal oxides selected from Ti, Mn, Zn, Al, and V; in the mixture, the molar ratio of the divalent iron element in the ferrous oxalate to the metal element in the metal element dopant is 1:(0.001~0.008); (2) The second carbon source is selected from one or more of glucose, starch, polyethylene, polyvinyl alcohol, polypropylene, and polyacryl alcohol; (3) The temperature of the heat treatment is 200℃ to 300℃, and the time of the heat treatment is 2h to 10h; (4) Before the heat treatment of the dried material, the dried material is pretreated by heating at 40°C to 140°C for 2 to 12 hours to remove the water of crystallization in ferrous oxalate. (5) The ferrous oxalate content in the slurry is 11% to 20% by weight; (6) The D50 particle size of the solid particles in the slurry is 260 nm to 400 nm; (7) The ball milling speed is 350 rpm to 450 rpm, and the ball milling time is 6 h to 10 h; (8) The lithium dihydrogen phosphate is prepared from a lithium source and a phosphorus source. The preparation of the lithium dihydrogen phosphate includes the following steps: dissolving the lithium source and the phosphorus source in water to obtain a first mixture, heating the first mixture at 60°C to 200°C to remove water, and obtaining the lithium dihydrogen phosphate; the lithium source is selected from one or more of lithium carbonate, lithium hydroxide, and lithium acetate, and the phosphorus source is selected from one or more of ammonium phosphate, monoammonium phosphate, and ammonium dihydrogen phosphate.
7. A lithium iron phosphate material, characterized in that, The lithium iron phosphate material is prepared from the lithium iron phosphate precursor material according to any one of claims 1 to 4, or from the lithium iron phosphate precursor material prepared by the method described in claim 5 or 6.
8. A method for preparing lithium iron phosphate material, characterized in that, The steps include: Under an inert gas atmosphere, the lithium iron phosphate precursor material according to any one of claims 1 to 4, or the lithium iron phosphate precursor material prepared by the preparation method of the lithium iron phosphate precursor material according to claim 5 or 6, is calcined at 450°C to 800°C for 2 to 10 hours to obtain the lithium iron phosphate material.
9. A positive electrode sheet, characterized in that, The positive electrode sheet comprises lithium iron phosphate material prepared by the method of preparing lithium iron phosphate precursor material according to claim 7 or claim 8.
10. A secondary battery, comprising a positive electrode, characterized in that, The positive electrode used is the positive electrode as described in claim 9.
Citation Information
Patent Citations
Preparation of lithium iron phosphate positive electrode material for lithium ion power cell
CN101339995A
Compound doped and cladded lithium ion cell anode material LiFePO4 and preparation method thereof
CN103346317A
Preparation method of composite carbon film wrapped lithium iron phosphate powder
CN103441277A
Preparation method of high performance lithium ion battery positive electrode material lithium iron phosphate
CN1948133A
A recovery method of lithium in black mass
KR1020260059816A